Investigating Potential Neglected Oil Reservoirs Using a New Approach - Putri Caesar, Athifa; Lestari; Wijayanti, Puri; Wihardjo, Lukas; Kadarusman, Sunarto (Journal of Earth Energy Science, Engineering, and Technology, 2024)
This research aims to explore the potential of neglected oil reservoirs through thin layer analysis. In this condition, drilling data based on oil base mud are used for analysis so that the effect of drilling mud invasion can be minimized. With the complete Oil Base Mud Imager (OBMI) Log Imager, the results of petrophysical calculations are compared based on standard logs, standard logs with resistivity from oil base mud imager, and using square log modeling for gamma ray, density, neutron and resistivity curves. From modeling and analysis of a 15 ft thick oil layer, the results show that PhiSo*H increases significantly. Based on the calculation results for the high-resolution resistivity log input, the PhiSo*H value has increased by 25% compared to the standard log input. Meanwhile, square log input increases the PhiSo*H value by 235% compared to standard log input. These indicate that there are thin oil layers that are not detected when using standard log input.